ASSESSMENT OF SERUM LEVELS OF GONADOTROPINS AND TESTOSTERONE IN PATIENTS WITH CHRONIC LUNG PATHOLOGY - Xamidovna, Mamatkulova Dilrabo (Research Focus International Scientific Journal, 2026)
Pubertal development was assessed and serum hormonal status was studied in patients with chronic lung disease (CLD). The study included 140 children with CLD. The results revealed significant differences in the timing of the onset of pubertal changes, the intensity of secondary sexual characteristics (SSC) development, and functional disturbances in the pituitary- gonadal axis, characterized by increased follicle-stimulating hormone (FSH) levels, decreased luteinizing hormone (LH), and decreased testosterone in boys with CLD. In girls with CLD, FSH levels were not significantly elevated at the onset of puberty. LH levels were significantly lower throughout puberty, and estradiol levels were significantly lower in older age groups. Thus, CLD negatively impacts the sexual development of children, necessitating the development of specific practical measures in this area.